2019
DOI: 10.1038/s41586-018-0858-8
|View full text |Cite
|
Sign up to set email alerts
|

Human blood vessel organoids as a model of diabetic vasculopathy

Abstract: The prevalence of diabetes is increasing constantly, resulting in a global epidemic 1 . Diabetes is a major cause of blindness, kidney failure, heart attacks, stroke or lower limb amputation; in large parts because of marked changes in blood vessels, defined by expansion of the basement membrane and a loss of vascular cells [2][3][4] . Diabetes also impairs endothelial cell (EC) function 5 and disturbs EC-pericyte communication 6 . How endothelial/pericyte dysfunction leads to diabetic vasculopathy remains lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
539
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 570 publications
(550 citation statements)
references
References 44 publications
9
539
0
2
Order By: Relevance
“…The pericyte represents a cell type of particular therapeutic interest, given its critical role in controlling BBB integrity via regulation of endothelial barrier function. Although not perfect mimics of the in vivo situation, organoid-based in vitro BBB systems for endothelium-pericyte interactions have recently been developed [171,172]. Pericytes exhibit plasticity after experimental injury [169], supporting the notion that their function may be improved or restored in an injury situation.…”
Section: Toward Therapy Developmentmentioning
confidence: 98%
“…The pericyte represents a cell type of particular therapeutic interest, given its critical role in controlling BBB integrity via regulation of endothelial barrier function. Although not perfect mimics of the in vivo situation, organoid-based in vitro BBB systems for endothelium-pericyte interactions have recently been developed [171,172]. Pericytes exhibit plasticity after experimental injury [169], supporting the notion that their function may be improved or restored in an injury situation.…”
Section: Toward Therapy Developmentmentioning
confidence: 98%
“…In an effort to model diabetic vasculopathy in vitro , a recent study reported the development of human blood vessel organoids from pluripotent stem cells that self‐assemble into capillary networks, containing endothelial cells and pericytes, surrounded by a basement membrane. Upon transplantation of these organoids into mice, a perfused vascular tree is formed, including arteries, arterioles and venules (Wimmer et al , ). These human blood vessel organoids may open new doors for PDTO co‐cultures.…”
Section: Integrating the Tumour Environment In Pdtx And Pdtomentioning
confidence: 99%
“…The graft will be better adapted to instantaneous perfusion, which in turn establishes a continued nutrient and oxygen delivery to the cells. Beyond this, newly emerging approaches, such as vascular organoids (Wimmer et al, 2019), may not only help us study vascularization in graft models but also potentially help establish a better graft vasculature. In conclusion, efforts should be made to integrate the currently available approaches by combining their strengths and eliminating their weaknesses.…”
Section: Discussionmentioning
confidence: 99%